2020
DOI: 10.32479/ijeep.8589
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Development of the Oil Industry in the Global Economy and in the Regional Economies

Abstract: This article analyzes global and regional development perspectives of the oil business. This study uses statistical, financial methods, as well as comparative approach to analyze modern state of the oil industry in the world and oil industry markets in various regions (OPEC, ОECD, Russia, etc.). Results show that current situation in the oil market is characterised by domination of those factors, which will facilitate maintenance of relatively low oil prices. The study develops oil market regulation model. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Its bottom layer is composed of multiple restricted Boltzmann machines, each of which is trained separately. The top layer is a BP neural network [ 3 , 11 ]. The bottom Boltzmann machine is trained by unsupervised learning, and the top BP neural network is trained by supervised learning.…”
Section: Relevant Theories Of In-depth Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Its bottom layer is composed of multiple restricted Boltzmann machines, each of which is trained separately. The top layer is a BP neural network [ 3 , 11 ]. The bottom Boltzmann machine is trained by unsupervised learning, and the top BP neural network is trained by supervised learning.…”
Section: Relevant Theories Of In-depth Learningmentioning
confidence: 99%
“…In the 1960s, when Hube and Wiesel studied cat visual cortex cells, they found that their neurons have a unique network structure and then proposed the concept of receptive field. In the 1980s, Fukushima proposed the neurocognitive machine model based on the inspiration of the wild theory [ 11 ]. Neurocognitive machines are also considered early convolutional neural networks.…”
Section: Relevant Theories Of In-depth Learningmentioning
confidence: 99%
“…The issues of business efficiency in the context of energy transition are in the field of scientific discussion, but most of the work explores the strategies of energy companies aimed at their "greening" [9], the economic feasibility of developing promising technologies [10], and low-carbon fuel production plants [11]. There are a number of papers that emphasize the idea of the need to make changes in general approaches to evaluating effectiveness [12,13]. Certain tensions and uncertainties caused do not negate the impact of the global trend of decarbonization and the need to take them into account.…”
Section: Introductionmentioning
confidence: 99%
“…e advent of the sequencing of sequential learning (Seq2Seq), in recent years, offers a more versatile and extensible temporal modelling system. e seq2seq model, however, suffers from the possible issue of the need to compact all historical data into an internal constant length vector [7]. is may restrict the seq2seq model's ability to manage long sequences.…”
Section: Introductionmentioning
confidence: 99%
“…is may restrict the seq2seq model's ability to manage long sequences. Methods for resolving basic Seq2Seq shortcomings and skills in modelling long-range dependencies, such as regional economic structures of longrange processes in the general environment, are therefore proposed for attention mechanisms [7].…”
Section: Introductionmentioning
confidence: 99%